2011
DOI: 10.3892/or.2011.1367
|View full text |Cite|
|
Sign up to set email alerts
|

Induction of apoptosis by casticin in cervical cancer cells through reactive oxygen species-mediated mitochondrial signaling pathways

Abstract: Abstract. Casticin, one of the main components from Fructus Viticis, has been reported to inhibit the growth of various cancer cells, including the human cervical cancer cell line HeLa. The purpose of this study was to examine the apoptotic activity and molecular mechanism of casticin action on human cervical cancer cells. The apoptotic activity of casticin on human cervical cancer HeLa, CasKi, SiHa and peripheral blood mononuclear cells (PBMCs) was measured using a histone/DNA ELISA assay, flow cytometry with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 35 publications
4
15
0
Order By: Relevance
“…However, previous studies also showed that the apoptosis-induced activity exerted by the natural plant extract or chemical compound is correlated with caspase-3 and caspase-9, but not caspase-8 [49,51,52] In the current study, the increase in cleaved caspase-3 and cleaved caspase-9 was verified by western blot compared with the control as cleaved caspase-8 was not found in BFTC cells after exposure to 13-acetoxysarcocrassolide. These results support the apoptosis-induced effects of 13-acetoxysarcocrassolide on BFTC cells displayed by flow cytometry and are in accordance with the evidence on caspase-3 and caspase-9-associated apoptosis shown previously [48,49,50,51,52]. Moreover, these data demonstrate that activation of caspase-3 and caspase-9 is likely involved in induction of apoptosis by 13-acetoxysarcocrassolide in BFTC cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, previous studies also showed that the apoptosis-induced activity exerted by the natural plant extract or chemical compound is correlated with caspase-3 and caspase-9, but not caspase-8 [49,51,52] In the current study, the increase in cleaved caspase-3 and cleaved caspase-9 was verified by western blot compared with the control as cleaved caspase-8 was not found in BFTC cells after exposure to 13-acetoxysarcocrassolide. These results support the apoptosis-induced effects of 13-acetoxysarcocrassolide on BFTC cells displayed by flow cytometry and are in accordance with the evidence on caspase-3 and caspase-9-associated apoptosis shown previously [48,49,50,51,52]. Moreover, these data demonstrate that activation of caspase-3 and caspase-9 is likely involved in induction of apoptosis by 13-acetoxysarcocrassolide in BFTC cells.…”
Section: Discussionsupporting
confidence: 92%
“…Another member of the caspase family, caspase-9, has also been shown to be associated with the induction of apoptosis in several cancer cells including cervical cancer cells, human hepatoma cells, melanoma cells, and human lung cancer cells. Interestingly, the activation of caspase-3 is tightly linked to the activation of caspase-9 in these anti-tumor studies [48,49,50,51,52]. However, previous studies also showed that the apoptosis-induced activity exerted by the natural plant extract or chemical compound is correlated with caspase-3 and caspase-9, but not caspase-8 [49,51,52] In the current study, the increase in cleaved caspase-3 and cleaved caspase-9 was verified by western blot compared with the control as cleaved caspase-8 was not found in BFTC cells after exposure to 13-acetoxysarcocrassolide.…”
Section: Discussionmentioning
confidence: 99%
“…Many natural products, such as casticin, curcumin, wogonin, Tanshinone IIA, and berberine, cause apoptosis through the mediation of ROS [2529]. Emodin and curcumin may sensitize cancer cell to anoikis through ROS generation [14, 22].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of FOXO3a by siRNA predominantly blocks casticin-induced apoptosis. Previous studies have demonstrated the antiproliferative and pro-apoptotic effects of casticin in prostate (10), cervical (14,15), lung (11) and colon (12) cancer. This study investigated the role of FOXO transcription factors in mediating the effects of casticin.…”
Section: Discussionmentioning
confidence: 99%
“…Casticin has also been reported to induce cell death of leukemia cells through the induction of apoptosis or mitotic catastrophe (13). We recently reported casticin-induced apoptosis of cervical cancer (14,15) and hepatocellular carcinoma (16) cells; however, the underlying mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%